Management of risk factors for gastrointestinal bleeding in patients receiving anticoagulant therapy - N. V. Bakulina; S. V. Tikhonov; N. B. Lishchuk; A. B. Karaya (Российский кардиологический журнал, 2021)
Direct oral anticoagulants (DOACs) are used to prevent and treat thrombosis and thromboembolic events in patients with various diseases. Despite its high efficacy and safety, DOAC therapy is accompanied by increased risk of hemorrhage, including gastrointestinal bleeding. Bleeding risk depends on individual patient profile and their risk factors. An increased risk of bleeding is associated with manifesting effect of DOACs on existing mucosal defects, active Helicobacter pylori infection. To reduce the risk of gastrointestinal bleeding in clinical practice, changing of following modifiable risk factors is required: H. pylori eradication; dose-adjusted DOAC therapy; prophylactic proton pump inhibitors (PPIs) administration to patients with HAS-BLED score ≥3, receiving dual or triple antithrombotic therapy, taking DOACs in combination with non-steroidal antiinflammatory drugs, to those with upper gastrointestinal diseases. In addition to PPIs, patients may be prescribed with rebamipide, bismuth tripotassium dicitrate, ursodeoxycholic acid. DOAC rivaroxaban (Xarelto®) has pharmacokinetic and pharmacodynamic advantages, a convenient single dosing regimen and a favorable safety profile, which provides effective protection against thrombosis and thromboembolic events in combination with low risk of gastrointestinal bleeding.